THE STUDENTS’ AND LECTURER’S PERCEPTION ON THE USE OF EDMODO APPLICATION AS MEDIA FOR LEARNING - Vina Apriwanti (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This article presents the students’ and lecturer’s perception on the use of Edmodo application as media for learning. The aims of this study was to figure out students’ and lecturer’s perception on the use of Edmodo application as media for learning. This research employed qualitative approach and used questionnaire as the instrument. The sample of this study was 16 that consist of 15 students and 1 lecturer. The finding of this research showed that 81,6% gained positive responses toward the use of Edmodo application as learning media. It contains of 55,2 % students agreed and 26,4% students are neutral about the effectiveness on the use this media to improve their comprehension skill about the course. Unfortunately, it also shows that 18,18% gained negative responses on students’ perceptions by features of Edmodo whether it can easy access for them or not. There are 17,6% students disagree, and 0,58% students strongly disagree. On the other hand, the researcher also investigated about lecturer’s perception on the use of Edmodo application. The questionnaire is filled in by only one lecturer. It gained positive responses that the use of Edmodo application is one of effectiveness way of English learning by provides a safe and secure environment in assignments for students.  In conclusion, most of students had positive attitudes towards the use of Edmodo application as their learning media. Lecturer agreed that the use of Edmodo assists in learning process. It has various features that is interesting to be used; quizzes were considered as one of fun and nice feature used during learning. Also the application was deemed to replace face to face discussion in quick and easy way through their smartphones. The lecturer also got benefit in sharing the material and other references just by one click, and also it has great and secure environment in learning for both students and lecturer.